The United States’ Engagement with International Law: An Analysis of the Social Complexities that Crystallized its Stance on Racial and Gender Rights - Womack, Malia Lee (La camera blu. Rivista di studi di genere, 2015)
The United States ratified the International Convention on the Elimination of all Forms of Racial Discrimination (ICERD) but has yet to sanction the Convention on the Elimination of all Forms of Discrimination Against Women (CEDAW). This article investigates what social costs drove the state to pass only one of the two anti-discrimination treaties. It finds that the state perceives the race convention to be less socially costly than the gender statute’s objective mandates in regards to content about social and cultural patterns, family planning resources, and in tensions about the proposed reservations, understandings, and declarations.